Scoping study of vegetable seedling systems in urban and peri-urban areas of Addis Ababa, Ethiopia - Adimassu, Zenebe; Coyne, Danny; Legesse, Wubetu Bihon (CGIAR System Organization, 2024)
Ethiopia's urban and peri-urban (UPU) vegetable production has grown significantly, enhancing food security and nutrition in densely populated areas. UPU agriculture reduces dependence on external food sources, lowers transportation costs, and provides fresh produce, thus improving dietary diversity and public health. It also empowers communities, creates jobs, and stimulates local economies. Access to quality seedlings is crucial to sustain urban agriculture and increase its productivity. Quality seedlings ensure vigorous growth and adaptability of vegetables, leading to a better nutrititive value and less use of chemical inputs, such as pesticides. This study assessed the functioning of vegetable seedling systems in UPU areas of Addis Ababa, Ethiopia. The study is based on in-depth interviews with 36 vegetable seedling producers and other key informants.